2021
DOI: 10.1515/ntrev-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

Development of ionic liquid-based electroactive polymer composites using nanotechnology

Abstract: This review is intended to provide an overview of the design and fabrication of ionic liquid-based ionic electroactive polymer (IL-iEAP) transducers for advanced applications in biological and electronic fields. The iEAP is a class of smart materials that can perform sensing or actuating functions by controlling the movement of cations and anions in the active layer. This type of material can deform under low voltage stimulation and generate electrical signals when undergoing mechanical deformation because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 152 publications
0
11
0
Order By: Relevance
“…Ionomeric Polymer Metal Composites (IPMCs) are electroactive materials that can perform bending movements in response to an electrical stimulus and vice-versa. They are based on an ion-exchange polymeric membrane between metallic electrodes 1 and have some interesting properties, such as low density, biocompatibility, and low driven voltage (< 5.00 V) 2,3 . For this reason, they are promising materials for a wide range of applications, such as actuators, sensors, and artificial muscles 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Ionomeric Polymer Metal Composites (IPMCs) are electroactive materials that can perform bending movements in response to an electrical stimulus and vice-versa. They are based on an ion-exchange polymeric membrane between metallic electrodes 1 and have some interesting properties, such as low density, biocompatibility, and low driven voltage (< 5.00 V) 2,3 . For this reason, they are promising materials for a wide range of applications, such as actuators, sensors, and artificial muscles 4 .…”
Section: Introductionmentioning
confidence: 99%
“…6,8,9 ILs, also known as green solvents with melting temperatures below 100 °C, are entirely composed of organic cations and organic/inorganic anions with properties such as negligible vapor pressure, high ionic conductivity, nonflammability, nonvolatility, and a wide electrochemical window (between 4 and 6 V). 10−12 The applicability of ILs in a wide range of areas is intrinsically related to the simple tunability of the physical−chemical properties by varying cations and anions, 6 a high number of possible cation and anion combinations existing, 10 leading to specific functional properties, including magnetic, electrical, and optical properties, among others. 6,13,14 Thus, ILs have been combined with specific polymers like poly(L-lactic acid) (PLLA), 15,16 cellulose, 16 poly(vinylidene fluoride) (PVDF), 17−21 and poly(methyl methacrylate) (PMMA), leading to a variety of functional characteristics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In fact, ILs have gained special attention in the last decade in several fields of knowledge due to their interesting properties. ,, ILs, also known as green solvents with melting temperatures below 100 °C, are entirely composed of organic cations and organic/inorganic anions with properties such as negligible vapor pressure, high ionic conductivity, nonflammability, nonvolatility, and a wide electrochemical window (between 4 and 6 V). The applicability of ILs in a wide range of areas is intrinsically related to the simple tunability of the physical–chemical properties by varying cations and anions, a high number of possible cation and anion combinations existing, leading to specific functional properties, including magnetic, electrical, and optical properties, among others. ,, …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ionic liquids (ILs), especially imidazole-type ILs, have been widely used as the ionic source in fabricating iEAPs due to their thermal and chemical stability, as well as non-volatility. 8–10 A large number of studies have reported that using ILs can effectively reduce the crystallinity and thus increase the amorphous phase and enhance the flexibility of polymers, facilitating larger deformation of the iEAPs. 11–13 Compared with other ILs, imidazolium chloride ILs at the same mass fraction provide polymers with better electrical properties and more flexibility.…”
Section: Introductionmentioning
confidence: 99%